Computational Analysis of Different Turbulence Models in a Vane Pump Simulation - Daniel Alberto Beleño Molina; Rafael Ramírez Restrepo; Jorge Eliecer Duarte Forero; Andrés David Rodríguez Toscano (Indonesian Journal of Science and Technology, 2021)
The study presents a computational analysis of a vane pump using two different turbulence models namely κ-ε and κ-ω. The geometry characteristics of the vane pump were obtained by disassembly and further measurements. The CAD model for the computational domain was developed in SOLIDWORKS®. The CFD modeling was powered by ANSYS®, which allowed the evaluation of different mesh types and turbulence models. A total set of six simulations were performed to obtain comparison schemes for turbulence model evaluation. Specifically, the angular velocity and excentricity were varied within the simulations. Both turbulence models were carefully validated using the manufacturer´s dataset as validation criteria, obtaining a relative error of less than 5%. The κ-ω experienced the best performance when describing the flow variables, excepting the pressure gradient. Specifically, the κ-ω presented an accurate prediction of edge effects, energy losses in the walls, and turbulent viscosity. Notably, the CFD modeling showed that density and velocity variations are not significant. Overall, CFD modeling demonstrated to be a robust tool to gain insight understanding of the flow interactions in vane pump operation.